How vertebrates left the water - Laurin, Michel (University of California Press, 2010)
This usefully illustrated book describes how some finned vertebrates acquired limbs, giving rise to more than 25,000 extant tetrapod species. Michel Laurin uses paleontological geological, physiological, and comparative anatomical data to describe this monumental event.